STRATEGI MUTU SDM BERBASIS BROAD BASED EDUCATION DAN HIGH BASED EDUCATION PADA LEMBAGA PENDIDIKAN NU: Perspektif Tantangan Abad ke-21 - SUBANDI, SUBANDI (Universitas Islam Negeri Raden Intan Lampung, 2017)
Although the educational program had been ongoing process since 68 years ago in Indonesia, but this state did not has provided qualified human resources. Since 32 years ago of the New Order Government authority, educational sector development has never been placed as a prime priority of development. The effect of Indonesian educational quality is being worse until now than the other countries in Southeast Asia likes Malaysia, Philippine, Singapore, and Thailand. Indonesia is being affected by dimensional multi crises since eighteen years ago and until now. It is still degraded by its past time which avoided educational development. Moreover, the other states which effected by the same problem like Indonesia could reform by paying attention greater toward educational development sector. They could reform faster and being better states because they have qualified human resources. By this broad based education system and high based education system, we hope the quality of Nahdliyin human resources will be better and qualified in the next future. Keywords: Human Resources Quality, Broad Based Education, High Broad education, Nahdliyin.